Redescription of Paracles vulpina (Hübner, [1825]) (Lepidoptera: Erebidae), with comments of the aquatic habit of larval instars - Beccacece, Hernán Mario; Viglione, Gabriela Bentancur; Graff, Pamela; Morelli, Enrique (Zootaxa, 2021)
The genus Paracles Walker, 1855 is one of the most diverse genera present in Arctiinae and some species have larvae with aquatic habits. Several larvae were found swimming in flooded areas in different grasslands and were bred to adults to identify the species: Paracles vulpina (Hübner, [1825]). The current knowledge of immature stages of this species is not useful to identify and discriminate from other species of Paracles. For this reason, we proposed to redescribe adults of P. vulpina, showing for the first time the male and female genitalia, and improve the information on the immature stages and their habits. The adults can be recognized by the whitish paler brown band in the costal area in the forewing and whitish paler brown antenna. The final larval stage of P. vulpina can be differentiated from other species because it shows a body with a black pubescence except for a ferruginous subventral pubescence, blue dorsal verrucae, red lateral verrucae, and dorsal plastron with longest white setae. Because of its polyphagous feeding habit on aquatic and non aquatic plants we consider the aquatic larval habit is not a necessary strategy and could depend on the ground topography or weather of the locality.